The existence of Murabahah in Bank Aceh Syariah based on the Fatwa of Majelis Ulama Indonesia No 111 /DSN-MUI/IX/2017 - Muhammad Rafi Thoriq; Muhammad Hasan Abdul Aziz Naibaho; Muhammad Alfain Faza Zakiyya (Mabadi Iqtishad Al Islami, 2024)
Financing in Islamic banks today is dominated by Murabahah contracts. The purpose of existing research is to explain how the existence of Murabahah financing in Islamic banking serves the community and assess whether the contracts executed comply with the Fatwa of Majelis Ulama Indonesia. This research is a library-research focused on examining and discussing modern and classical literature. Data collection is conducted through documentation methods from various sources including national and international journals, as well as books. The data is then analyzed using content analysis, which includes descriptive analysis and scientific analysis of premium messages. The findings of this research indicate that Murabahah financing is predominantly conducted by Islamic banks for community financing. In the application of Murabahah financing, Islamic banks act as fund providers rather than sellers. The Murabahah contracts in classical fiqh have undergone changes, which have been criticized by various segments of society. It is noted that there are contemporary issues arising in Murabahah financing transactions that do not align with Sharia principles and the Fatwa of Majelis Ulama Indonesia.